Numerical study on the dynamic migration and distribution characteristics of impurity particles in jet fuel settling tanks during different operation conditions - Lin Mu; Xin Zhao; Junfeng Zhao; Yan Shang; Ming Dong (Results in Engineering, 2025)
Jet fuel settling can effectively improve the cleanliness of jet fuel. In the process of low-level oil delivery operation of jet fuel settling tank, the oil delivery pipe will inevitably disturb the impurity particles settled at the bottom of the tank, it is difficult to ensure the cleanliness of jet fuel because the impurity particles are pumped out of the tank. In view of the above problems, the dynamic characteristics of single impurity particles, the flow field distribution in the tank and the distribution characteristics of impurity particles are studied by numerical simulation. For single spherical particles, the particles do variable acceleration motion at the bottom of the tank. When the particle size and density exceed 150 μm and 5000 kg·m-3 respectively, the particles will be difficult to start, heavy particles will concentrate in the bottom center of the tank. For non-spherical particles, the influence of particle shape on the drag coefficient is significant, and the order is tetrahedron > cylinder > cube > sphere > ellipsoid. Particle drag coefficient decreases with increasing particle Reynolds number Res. For small pipe diameter, low oil delivery speed and high liquid level conditions, jet fuel will form a reflux vortex in the central area of the tank, and the vortex will continue to spread along the radial direction with the advance of the operation time. Light particles will do a closed-loop flow with the vortex, and heavy particles will diffuse radially at the bottom of the tank, resulting in a decrease in particle concentration in the center of the tank bottom. This study provides theoretical guidance for controlling the intake of impurity particles and optimizing oil discharge conditions.